Pharmacotherapy in Mental Disorders: Critical Reconsideration - M. M. Reshetnikov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In this paper, traditional concepts of on link between mental activity and brain activity are reviewed, and hypothesis of brain as a biological interface, which was earlier (2008) suggested by the author, is developed. Approaches to research of psyche in areas of physiology, psychology and psychiatry, as well as their applications to therapy of patients with mental disorders, are analysed. The author suggests two main models of mental disorders based on clearer differentiation of organic (brain) pathology and mental disorders as such that result from informational non-material influence on psyche rather than on brain. Difference between nervous and psychic functioning of organism and personality is outlined; mental activity is viewed as an acquired or programmed function formed in social informational environment.